Dionis: A Novel Remote-Center-of-Motion Parallel Manipulator for Minimally Invasive Surgery - R. Beira; L. Santos-Carreras; G. Rognini; H. Bleuler; R. Clavel (Applied Bionics and Biomechanics)
The large volume and reduced dexterity of current surgical robotic systems are factors that restrict their effective performance. To improve the usefulness of surgical robots in minimally invasive surgery (MIS), a compact and accurate positioning mechanism, named Dionis, is proposed in this paper. This spatial hybrid mechanism based on a novel parallel kinematics is able to provide three rotations and one translation for single port procedures. The corresponding axes intersect at a remote center of rotation (RCM) that is the MIS entry port. Another important feature of the proposed positioning manipulator is that it can be placed below the operating table plane, allowing a quick and direct access to the patient, without removing the robotic system. This, besides saving precious space in the operating room, may improve safety over existing solutions. The conceptual design of Dionis is presented in this paper. Solutions for the inverse and direct kinematics are developed, as well as the analytical workspace and singularity analysis. Due to its unique design and kinematics, the proposed mechanism is highly compact, stiff and its dexterity fullfils the workspace specifications for MIS procedures.